Denis de Rougemont: la persona, l’europeismo, la politica. - Melchionni, Maria Grazia (Rivista di studi politici internazionali, 2008)
ABSTRACT - Soon after the centenary of Denis de Rougemont’s birth, which was remembered by the RSPI but went off quite silently in Italy, the Author highlights the main features of this outstanding personality and the originality of his contributions to literature, philosophy and politics of XXth century’s Europe. The article is focused on de Rougemont’s path to federalism and the evolution of his political thought and strategy, from the idea of choosing culture to forward European building to the purpose of backing the environmentalists in the search for another Europe. RÉSUMÉ - Au lendemain du centenaire de la naissance de Denis de Rougemont, que la RSPI a rappelé mais qui s’est passé presqu’en silence en Italie, cet article souligne les traits principaux de cette personnalité remarquable, qui apporta des contributions originales à la littérature européenne et à la pensée philosophique et politique de son temps. L’attention de l’Auteur est tournée vers le parcours fédéraliste de Denis de Rougemont et s’étend, en particulier, sur sa vision concernant le rôle de la culture dans la construction européenne et, à la fin, sur son penchant pour l’Europe des écologistes.